Current multimodal diagnostic tools for diabetic macular edema to select a management strategy - M.V. Pshenichnov (РМЖ "Клиническая офтальмология")
M.V. Pshenichnov Khabarovsk Branch of the S. Fedorov Eye Microsurgery Federal State Institution, Khabarovsk, Russian Federation Diabetes is a severe chronic disease that significantly affects the quality of life of individuals, their families, and society worldwide. Diabetic retinopathy, particularly diabetic macular edema (DME), is the leading cause of blindness and low vision among adults of working age in developed countries and Russia. A recent multimodal approach to diagnose DME resulted in new classifications of this disorder and slightly modified earlier views. The analysis of DME biomarkers allows for selecting management strategies for each patient, prescribing adequate medical treatment, and predicting potential treatment response. This paper aimed to analyze published data and up-to-date diagnostic approaches to DME. These tools provide a correct therapeutic strategy based on the DME pattern. Keywords: diabetic macular edema, optical coherence tomography, anti-VEGF treatment. For citation: Pshenichnov M.V. Current multimodal diagnostic tools for diabetic macular edema to select a management strategy. Russian Journal of Clinical Ophthalmology. 2021;21(4):210–214 (in Russ.). DOI: 10.32364/2311-7729-2021-21-4-210-214.